2007
DOI: 10.1007/s12016-007-8024-3
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab Induces Distinct Intraorbital and Intrathyroidal Effects in One Patient Satisfactorily Treated for Graves’ Ophthalmopathy

Abstract: Hyperthyroid Graves' disease (GD) is a B-cell-mediated disease caused by antibodies stimulating the thyroid stimulating hormone (TSH) receptor (TRAb). A proportion of patients (40-60%) present with an associated ophthalmopathy (TAO), a progressive inflammatory autoimmune disease of the retroorbital tissue. We thought that the anti-CD20 monoclonal antibody rituximab (RTX), by inducing transient B-cell depletion, may potentially modify the active inflammatory phase of TAO. One patient with GD and TAO in its acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…CD20 is expressed on the surface of pre-Band mature B-lymphocytes (12), and rituximab shows no direct effects on plasma cells producing immunoglobulins. This drug has been reported to show a favorable outcome in the treatment of malignant lymphoma and autoimmune diseases, including SPS and dysthyroid ophthalmopathy (9,(13)(14)(15)(16)(17). In the present patient also, intermittent administrations of rituximab produced obvious improvement of both SPS and dysthyroid ophthalmopathy with a persistent decrease in the anti-GAD and anti-thyroid antibodies.…”
Section: Stiff-person Syndrome (Sps) Is a Rare Intractable Disorder Csupporting
confidence: 56%
See 1 more Smart Citation
“…CD20 is expressed on the surface of pre-Band mature B-lymphocytes (12), and rituximab shows no direct effects on plasma cells producing immunoglobulins. This drug has been reported to show a favorable outcome in the treatment of malignant lymphoma and autoimmune diseases, including SPS and dysthyroid ophthalmopathy (9,(13)(14)(15)(16)(17). In the present patient also, intermittent administrations of rituximab produced obvious improvement of both SPS and dysthyroid ophthalmopathy with a persistent decrease in the anti-GAD and anti-thyroid antibodies.…”
Section: Stiff-person Syndrome (Sps) Is a Rare Intractable Disorder Csupporting
confidence: 56%
“…In the present patient also, intermittent administrations of rituximab produced obvious improvement of both SPS and dysthyroid ophthalmopathy with a persistent decrease in the anti-GAD and anti-thyroid antibodies. According to the recommended therapeutic protocol for autoimmune disorders, including dysthyroid ophthalmopathy, rituximab is usually given twice at an interval of 2 weeks (13,14) …”
Section: Stiff-person Syndrome (Sps) Is a Rare Intractable Disorder Cmentioning
confidence: 99%
“…Another explanation for the same CAS improvement in both groups (rituximab versus placebo) in the latter study could be the effect of the natural course of GO as a self-limiting autoimmune disease. However, several case report studies demonstrated the relationship between rituximab administration and a decrease of inflammatory orbital infiltration, particularly complete depletion of CD20+ lymphocytes [11,14,17]. Significant changes of 99m Tclabelled diethylenetriaminepentaacetic acid orbital uptake and of T2 relaxation times of extraocular muscles on magnetic resonance imaging showing the effect of rituximab treatment for GO were also reported [18].…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, the experience with Rituximab (RTX), a chimeric mouse monoclonal anti-human CD20 antibody that blocks B-cell proliferation and maturation is encouraging. [35][36][37][38] Salvi et al 38 , using parenteral RTX in a non-randomised cohort of nine patients with active TED, reported a greater improvement in clinical activity after RTX (1000 mg intravenous infusion, twice at two-week interval), and with fewer side effects, than those treated with a standard intravenous glucocorticoid regimen (500 mg i.v. weekly for 16 weeks).…”
Section: Moderate To Severe Tedmentioning
confidence: 99%